2022
DOI: 10.1038/s41380-022-01442-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I mitigates post-traumatic stress by inhibiting AMP-kinase in orexin neurons

Abstract: Maladaptive coping behaviors are probably involved in post-traumatic stress disorders (PTSD), but underlying mechanisms are incompletely understood. We now report that mice lacking functional insulin-like growth factor I (IGF-I) receptors in orexin neurons of the lateral hypothalamus (Firoc mice) are unresponsive to the anxiolytic actions of IGF-I and develop PTSD-like behavior that is ameliorated by inhibition of orexin neurons. Conversely, systemic IGF-I treatment ameliorated PTSD-like behavior in a wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…We also showed that Firoc mice under 6 h restricted feeding during the resting phase, a strong food clock entrainment, showed enhanced food anticipatory activity. These results agree with previous ones from our laboratory, showing increased orexinergic activity in Firoc mice undergoing cued behavior paradigms [40]. The FAA phenomenon is independent of the SCN [54][55][56], and only lesions in the DMH abolished it [55].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We also showed that Firoc mice under 6 h restricted feeding during the resting phase, a strong food clock entrainment, showed enhanced food anticipatory activity. These results agree with previous ones from our laboratory, showing increased orexinergic activity in Firoc mice undergoing cued behavior paradigms [40]. The FAA phenomenon is independent of the SCN [54][55][56], and only lesions in the DMH abolished it [55].…”
Section: Discussionsupporting
confidence: 93%
“…Hence, altered orexin activity could be related to IGF-I dysregulation due to aging, diet, or pathology. These results indicate that IGF-I regulates orexin neurons, and, consequently, circadian rhythms and metabolism, extending and confirming previous observations on central actions of IGF-I on mood, metabolism, and wellness [29,40].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations